2010
DOI: 10.1590/s1677-55382010000100004
|View full text |Cite
|
Sign up to set email alerts
|

Diffusion weighted imaging in the detection of upper urinary tract urothelial tumors

Abstract: Purpose: Diffusion-weighted (DW) magnetic resonance imaging (MRI) provides information about the biophysical properties of tissues such as cell organization and density. DW imaging (DWI) is becoming important in the assessment of malignant tumors. The purpose of our study was to evaluate the capability and reliability of DWI in the evaluation of upper urinary tract urothelial tumors. Materials and Methods: DWI was performed in seventeen patients with upper urinary tract urothelial tumor, previously diagnosed b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(9 citation statements)
references
References 20 publications
0
8
0
1
Order By: Relevance
“…6 Although upper tract infiltrating urothelial carcinomas have been relatively well described in pathology and imaging studies, IRPUC is scanty. 7,8 Some imaging features have been reported, such as infiltrative growth 9 and cystic component. However, some imaging features remain uncertain or contradictory, such as tumour location, capsule sign, calcification and enhancement pattern.…”
Section: Discussionmentioning
confidence: 99%
“…6 Although upper tract infiltrating urothelial carcinomas have been relatively well described in pathology and imaging studies, IRPUC is scanty. 7,8 Some imaging features have been reported, such as infiltrative growth 9 and cystic component. However, some imaging features remain uncertain or contradictory, such as tumour location, capsule sign, calcification and enhancement pattern.…”
Section: Discussionmentioning
confidence: 99%
“…[11] DW-MRI is used in several urological malignancies, such as prostate cancer, upper urinary tract cancer, and kidney cancer. [12,13] In bladder cancer, several studies have shown that the accuracy of T staging with DW-MRI exceeds that of conventional methods. [2,[4][5][6] We also showed that DW-MRI provides significant additional information for the T staging of bladder cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Since that report, several studies have reported on the application of DW‐MRI in the management of UTUC, consistently showing excellent diagnostic performance (Table ) . In retrospective studies including patients with known UTUC cancers, the sensitivity of DW‐MRI in detecting UTUC was reported to be 88.9–100% .…”
Section: Clinical Applications Of Dw‐mri In Upper Urinary Tract Cancermentioning
confidence: 94%